Doppler assessment of the ductus venosus and the tricuspid valve at 11–13+6 weeks: Reference ranges and development of sonographic quality assurance standards. Issue 1 (February 2016) - Pincham, Vanessa; Hyett, Jon; Pollard, Karen; Schluter, Philip; McLennan, Andrew
Abstract: Objective: To develop reference ranges for the ductus venosus (DV) and tricuspid valve (TV) waveforms at 11–14 weeks and define auditable standards to assess operator measurement performance. Materials and methods: A single operator prospectively obtained quantitative measurements of a number of DV and TV Doppler indices to develop medians and 90% reference intervals (RIs). Measurement agreement studies between two experienced operators were also performed. The measurement bias of three additional operators was subsequently assessed using the newly defined auditable standards. Results: Doppler measurements were obtained in 292 patients (DV) and 321 patients (TV). Reference ranges were constructed for DV pulsatility index for veins (PIV) which did not change over gestation (mean 1.06; 90% RI 0.86–1.23) and for the TV E–A ratio reference range which was positively correlated with gestation. Measurement agreement studies on 30 additional patients showed the within‐operator agreement was almost perfect for DV PIV (ICC, intraclass correlation 0.82–0.86) and strong for TV E–A ratio (ICC 0.68–0.78) while the between‐operator agreement was good for both DV PIV and TV E–A ratio measurements (ICC 0.46 for both). Discussion: Development of local reference ranges enabled the definition of quantitative auditable standards that can be utilised in assessment of operator training and ongoing Doppler measurement quality assurance. Measurements of DV PIV and TV E–A ratio by experienced operators were found to be reproducible.